2010
DOI: 10.1111/j.1750-3841.2010.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Roasting Affects Phenolic Composition and Antioxidative Activity of Hazelnuts (Corylus avellana L.)

Abstract: The potential effect of skin removal and roasting on individual and total phenolic content, and on antioxidative potential of 6 hazelnut cultivars were investigated. HPLC-MS identification of individual phenolics confirmed the presence of 7 flavan-3-ols (catechin, epicatechin, 2 procyanidin dimers, and 3 procyanidin trimers), 3 flavonols (quercetin pentoside, quercetin-3-O-rhamnoside, and myricetin-3-O-rhamnoside), 2 hydrobenzoic acids (gallic acid, protocatechulic acid), and 1 dihydrochalcone (phloretin-2'-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 26 publications
4
70
1
Order By: Relevance
“…Hazelnuts. Schmitzer et al (91) reported that roasting had a negative effect on individual phenolics but not on the total phenolic content and TAC (determined by DPPH) of hazelnuts. They found that the roasting decreased protocatechulic acid, phloretin-2-O-glucoside, catechin and epicatechin contents in whole hazelnuts of six genotypes harvested in Maribor, Slovenia.…”
Section: Post-harvest Factorsmentioning
confidence: 99%
“…Hazelnuts. Schmitzer et al (91) reported that roasting had a negative effect on individual phenolics but not on the total phenolic content and TAC (determined by DPPH) of hazelnuts. They found that the roasting decreased protocatechulic acid, phloretin-2-O-glucoside, catechin and epicatechin contents in whole hazelnuts of six genotypes harvested in Maribor, Slovenia.…”
Section: Post-harvest Factorsmentioning
confidence: 99%
“…According to the daily microelement requirements, 100 g of Turkish hazelnut cultivars has supplied about 50% for Fe and Cd, 41% for Mo, 32% for Zn, 21% for Se, 21% for Cr, 5% for B, 1% for Ni of the recommended daily amount (Özkutlu et al, 2011). Hazelnut is the best source of essential elements, amino acids, vitamin B and E among tree nuts (Açkurt et al, 1999;Oliveira et al, 2008;Xu and Hanna, 2011) and serves as a good source of natural antioxidants (Açkurt et al, 1999;Contini et al, 2008;Schmitzer et al, 2011). Several studies indicated that the nut composition of hazelnut is affected by cultivar, harvest year, soil and geographical origin (Açkurt et al, 1999;Amaral et al, 2006;Dundar et al, 2002;Seyhan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hazelnut fruits are different in morphologic characteristics and mineral composition with an extremely high variability among genotypes of different origins (Ferreira et al, 2010;Rovira et al, 2005). They are a rich source of main nutritive matter that seem to have positive effect on human health (Cristofori et al, 2008;Oliveira et al, 2008;Schmitzer et al, 2011;Silva et al, 2007). Regarding mineral composition, Alasalvar et al (2003) considered that the major minerals in hazelnut were potassium, phosphorus, calcium, magnesium, and selenium.…”
Section: Introductionmentioning
confidence: 99%
“…Duration of cooking and methods also have been found to have a negative impact on phenolic content and antioxidant activity (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%